First report of Lasiodiplodia theobromae and Pseudofusicoccum stromaticum causing dieback in Syzygium malaccense tree in Brazil. Issue 2 (19th December 2017) - Silveira, G. F.; Melo, M. P.; Teixeira, J. W. M.; Viana, D. C.; Silva, J. D. C.; Beserra, J. E. A.
Summary: Syzygium malaccense is a woody species, known as Malay apple, which is grown as an ornamental or for fruit production in Brazil, mainly in the northern and north‐eastern regions. A high incidence of dieback has been observed in Malay apple in ornamental situations, including streets and gardens. Morphological identification, sequencing analysis of TEF+ITS gene regions and a pathogenicity test confirmed that fungi in the Botryosphaeriaceae cause the disease. This is the first report of Lasiodiplodia theobromae and Pseudofusicoccum stromaticum causing dieback on S. malaccense trees in Brazil.